IMPLEMENTASI APLIKASI WEB BASED LEARNING DENGAN MEDIA VIDEO TUTORIAL PADA MATA KULIAH JARINGAN KOMPUTER - Kurniawan, Haris; Darman, Regina Ade; Devegi, Mourend (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
ABSTRACT Learning by utilizing Information and Communication Technology (ICT) is one of the e-learning models that is needed now and in the future. The lack of optimal class hours and facilities and infrastructure causes less effective learning which has an impact on low learning outcomes. By implementing web-based learning applications with video tutorial media, it is hoped that it can affect the learning outcomes of computer network and data communication courses for informatics education study program students at PGRI University of West Sumatra. This research is an experiment using a randomized posttest only control group design. The experimental class used web-based learning application treatment with video tutorial media while the control class without video tutorial media. The research population was students of the 2021 informatics education study program. The instrument used is a test question. The data analysis technique uses the t test which is obtained t count is 2.13 and t table is 1.68, thus t count > t table which means the hypothesis is accepted. In this study, it can be concluded that there is a significant effect of using web-based learning applications with video tutorial media on learning outcomes.